PELAKSANAAN INOVASI LAYANAN POJOK BRAILLE (LAPO BRA) DALAM MENINGKATKAN PELAYANAN PUBLIK (Studi pada Dinas Perpustakaan Umum dan Arsip Daerah Kota Malang) - Florentina Nduet (Universitas Tribhuwana Tunggadewi, 2019)
The Office of the Public Library and Regional Archives of Malang City in order to improve public services which launched a service called the Braille Corner Service (Lapo Bra), which is intended for blind persons with disabilities where they can enjoy the same services as the general public. The purpose of this study was to learn how to implement